On Hegel’s Concept of Culture (Bildung) - Poviliūnas, Arūnas (Problemos, 1988)
Despite the absence of the term “culture” in Hegel’s works his concept of culture is often analysed in the philosophy of culture. In the article the possibility to interpret Hegelian term “Bildung” as “culture” is being discussed. Hegel’s concept of culture (Bildung) is defined as the process of alienation of Dasein, i.e., as the formation of self-consciousness.